KEMAMPUAN PENALARAN SISWA SMA DALAM PEMBUATAN KLADOGRAM PADA MATERI PLANTAE - Hanatul Haifa Kurnia, - (2022)
Based on National Curriculum 2013 revised 2020, the ability to reason is one of the important abilities that students must have. Various studies have attempted to identify the ideal learning in improving student's reasoning abilities. Making a cladogram to classify plants in Plante is an ideal biological material to test student's reasoning abilities. Therefore, the purpose of this study is to analyze whether learning to make cladograms on Plantae material can affect student's reasoning abilities. The extent to which students' reasoning abilities apply from the application of this learning. Participants consisted of 53 students from grade X in one of the high schools in Bandung. Students are asked to provide answers in the form of claims and supporting reasons, then the data is collected, processed, and analyzed. The research method used is quantitative. The research data is based on the results of the pretest-posttest as many as 23 questions, worksheets, learning implementation observation sheets, and student responses to learning to make cladograms on Plantae material. The results showed that students' reasoning abilities increased significantly after learning to make caldograms on Plantae material, this was indicated by the N-gain value of 0.57 which was included in the medium category. Before learning to make cladograms, the dominant students' reasoning categories were at levels 0 and 1, there was no assessment category or only claims. While learning to make cladograms on Plantae material, the dominant category of student reasoning is formed and increased at levels 3 and 4, namely reasoning skills based on data and reasoning based on evidence.